2018
DOI: 10.3233/jad-170329
|View full text |Cite
|
Sign up to set email alerts
|

Early Stage Alterations in CA1 Extracellular Region Proteins Indicate Dysregulation of IL6 and Iron Homeostasis in the 5XFAD Alzheimer’s Disease Mouse Model

Abstract: In recent years, an increasing number of research papers revealed that the compositional and volumetric alterations in the extracellular matrix are the consequences of aging and may be related to Alzheimer's disease (AD). In this study, we aimed to demonstrate the alterations in hippocampal extracellular fluid proteins in vivo using the 5XFAD mouse model. Samples were obtained from hippocampi of 5XFAD mice (n = 6) and their non-transgenic littermates by intracerebral push-pull perfusion technique at 3 months o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 59 publications
0
12
1
Order By: Relevance
“…Significant differences in proinflammatory chemokines secreted by astrocytes have been proved between AD patients and normal aged people (Liu et al, 2015 ). A reduction in gene expression for Il-6 and Tnf-α in 5xFAD-EE mice suggested a reduction in the inflammatory process in 5xFAD (Gurel et al, 2018 ). The lower inflammation after EE was also reinforced by a diminution in astroglial activation after EE demonstrated a significant decrease in Gfap gene expression and protein levels (Brahmachari et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences in proinflammatory chemokines secreted by astrocytes have been proved between AD patients and normal aged people (Liu et al, 2015 ). A reduction in gene expression for Il-6 and Tnf-α in 5xFAD-EE mice suggested a reduction in the inflammatory process in 5xFAD (Gurel et al, 2018 ). The lower inflammation after EE was also reinforced by a diminution in astroglial activation after EE demonstrated a significant decrease in Gfap gene expression and protein levels (Brahmachari et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to iron load, inflammation is also being recognized as an important pathogenic marker of neurodegenerative diseases. It is observed early in AD and PD, often bearing evidence of peripheral (intestinal) aberrant response to different stimuli ( Qin et al, 2016 ; Houser and Tansey, 2017 ; Raj et al, 2017 ; Gelders et al, 2018 ; Gurel et al, 2018 ; King et al, 2018 ; Steeland et al, 2018 ). This means that in AD and PD the pathogenic process is initiated and “fueled” by immunologic disturbances occurring in the gastrointestinal tract.…”
Section: Role Of Inflammation and Iron Load In Neurodegenerative Disementioning
confidence: 99%
“…We also observed that several inhibitors of serine proteases (serpins) appear to progressively decrease in expression during the monitoring period. Interestingly, a recent study of the hippocampal proteome in the 5 × FAD mouse model of AD also identified downregulation of serpins (Gurel et al, 2018). Protease inhibitors hold a potential as therapeutic targets since their levels in the brain can be restored through injection of recombinant protein.…”
Section: Discussionmentioning
confidence: 99%